A new species of Neosclerocalyptus Paula Couto (Mammalia: Xenarthra: Cingulata): the oldest record of the genus and morphological and phylogenetic aspects - Zurita, Alfredo E.; Taglioretti, Matias; Zamorano, Martin; Scillato-Yané, Gustavo J.; Luna, Carlos; Boh, Daniel; Saffer, Ariano Magnussen (Zootaxa, 2013)
Among South American Quaternary Glyptodontidae (Mammalia, Cingulata), Neosclerocalyptus Paula Couto represents one of the best known genera. Prior to this contribution, four species were recognized. N. pseudornatus (Ameghino) and N. ornatus (Owen) (Ensenadan Age/Stage, early-middle Pleistocene); N. gouldi Zurita (Bonaerian Age/Stage, middle Pleistocene-late Pleistocene), and N. paskoensis (Zurita) (Lujanian Age/Stage, late Pleistocene-early Holocene). One of the most notable characters of the species of the genus is a modified area located in the distal part of the nasals, recently interpreted as a neomorphic structure derived from the ossification of the nasal cartilages. In this contribution, a new species of Neosclerocalyptus (N. castellanosi sp. nov.), which in turn represents the oldest record of the genus, is presented and described. In addition, a cladistic analysis is carried out to test the monophyly of Neosclerocalyptus and the phylogenetic position of this new species. The material comes from Vorohuean (late Pliocene) levels in the surroundings of Mar del Plata, Buenos Aires Province, Argentina. Among other morphological characters, this new species has ossified nasal cartilages restricted to the latero-dorsal area of the nasals, whereas in the remaining species these structures are more expanded and both sides contact in the midline of the skull. In turn, the phylogenetic analysis confirmed the monophyly of Neosclerocalyptus, whereas N. castellanosi  sp. nov. appears closely related to N. pseudornatus, being N. ornatus the sister taxa of this clade. On the other hand, N. gouldi + N. paskoensis constitute the other clade. The clade constituted by Hoplophorus euphractus Lund + Panochthus intermedius Lydekker constitutes the sister taxa of Neosclerocalyptus.